Konsumsi Rokok Masyarakat Kota Bandung Tahun 2015 dengan Model Hurdle Negatif Binomial (Hurdle-Nb) - Wulandari Wulandari; Wida Tira Tedra; Irtania Muthia Rizki; Dina Prariesa (Jurnal Aplikasi Statistika & Komputasi Statistik, 2017)
Lifestyle that high risk to health is smoking behavior. Smoking behavior has a negative impact on health, both for active smokers and passive smokers. In addition there are also negative impacts in terms of economy. In Bandung, spending on cigarettes ranks second after the food commodity. The number of cigarettes smoked each day is influenced by demographic variables, social environment variables, political variables, and cultural variables. In this study, the Bandung cigarette consumption and the factors suspected to affect, ie sex, age, work status, and education, will be modeled by Hurdle-NB regression. The results showed that Log model, age variable, work status, and education influence to the average of cigarette consumption. While on Logit model, gender variable, age, work status, and education have an effect on the tendency of someone to smoke or not.